Connections Matter: Implicit infrastructures and Electricity Access in Witsand, Cape Town - Dipura, Romeo (Department of Environmental and Geographical Science, 2023)
For most residents living in Wits and, on Cape Town's north-western urban periphery, electricity access involves piecing together electricity wires and connecting them to Eskom transmission lines or tampering with Eskom prepaid meters and recharging with cheaper black market electricity vouchers. These practices require residents to circumvent Eskom's vouchers and prepaid meters in order to adapt Eskom electricity to their lived realities. In a context where Eskom electricity provision is sometimes absent, often unreliable, and largely unaffordable, residents engage diverse strategies to take charge of their own electricity inclusion. This research draws on over twenty months of fine-grained ethnographic work in Wits and, where I reside, which included journaling, transect walks, to map typologies of connections, participant observations, and semi structured interviews. Building on Storeys' (2021) notion of ‘implicit' infrastructures, in this thesis I substantiate how resident-made electricity connections prove a critical, although implicit, part of the wider electricity infrastructure system. While these connections are essential for residents' access, they are also dangerous and unsanctioned by Eskom. Resident-made electricity connections involve enduring bodily, material, legal and relational risks. These risks range from resident electrocutions and house-fires to Eskom penalties and disconnections. Drawing on a sociotechnical approach to infrastructure, I use the notion of ‘precarious power' to explore the mix of agency and precariousness that are entangled in the everyday practices of ordinary people making electricity connections. I argue that in improvising electricity access, residents in Wits and exercised their agency to circumvent, adapt and appropriate Eskom electricity. Yet in doing this they simultaneously endured the precariousness of the daily labors, bodily risks and contestations associated with their practices. In making this argument, I contribute to an understanding of urban residents' everyday infrastructural experiences through an analytical frame that is neither dismissive of their agency nor celebratory of their struggles.